Modification of Conductive Polymer for Polymeric Anodes of Flexible Organic Light-Emitting Diodes - Wang, Guang-Feng (Springer, 2009)
A conductive polymer, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS), was modified with dimethyl sulfoxide (DMSO) in solution state, together with sub-sequential thermal treatment of its spin-coated film. The electrical conductivity increased by more than three orders of magnitude improvement was achieved. The mechanism for the conductivity improvement was studied at nanoscale by particle size analysis, field emission scanning electron microscopy (FESEM), and X-ray photoelectron spectroscopy (XPS). Smaller particle size was observed, resulting in larger contact area and better electrical conductive connections. Connection of conductive PEDOT increased on the surface of the PEDOT:PSS particles, which promoted high conductivity. Flexible anodes based on the modified PEDOT:PSS were fabricated. Flexible organic light-emitting diodes (FOLED) based the polymeric anodes have a comparable performance to those on indium–tin–oxide (ITO) anodes.